EXECUTIVE DASHBOARD PENILAIAN KINERJA DOSEN PADA STMIK KHARISMA MAKASSAR - Ariangga; Abdullah; Moh. Sofyan S. Thayf (KHARISMA Tech, 2019)
The problem in STMIK KHARISMA Makassar in this study is because the management of lecturer evaluations is only in the form of distributing questionnaires on lecture evaluations and does not produce a value that can be used as a reference for lecturers’ performance. The purpose of this study is the application of new performance appraisals and creating applications that can provide visual information for lecturers’ performance. The application that is built is a website that uses the PHP programming language and MySQL database. Data collection is done by conducting interviews and distributing questionnaires to determine the condition of the problem. From the results of the analysis obtained if perceptional assessment can be used as a standard assessment that has included the assessment of students, colleagues, and leaders. From the results of testing the application, it is known if the dashboard with perceptional assessment can provide information on the performance of the lecturer and provide an overview of how the lecturer performs. And then, from the information on the results of the persepsional assessment can be used for the needs of leaders in making decisions or others.